Le pseudonyme chez la communauté d’internautes algériens sur le web social : quels choix et quels enjeux sociolinguistiques ? - Achour Bourdache; Soufiane Lanseur (Multilinguales)
The pseudonym as an anthroponymic category is a social practice in which the interest of researchers in the field of popular onomastics and sociolinguistics is almost minimal, hence, in particular, the scarcity of research devoted to it. This contribution comes precisely, against the tide of this renewed interest manifested in this anthroponomastic category. It deals with the socio-identity and sociolinguistic choices and issues of the pseudonym of a community of Internet users. The main problem is to determine what motivations and sociolinguistic, identity criteria… presiding over the choice of pseudonyms in the Algerian community and what uses this community of the pseudonym makes of it and in what contexts. The article concludes, through a socio-onomastic analysis and the exploitation of mental discourses from a sociolinguistic perspective, that the choice of pseudonym is made in various onomastic and linguistic registers. It is determined by a multitude of criteria and personal, socio-identity and symbolic determinations of the community in question and whose use has extended from the social web Facebook to the social sphere of the subject-user by becoming an appellation in address in specific social backgrounds.